Vaginal Birth at Term - Part 2Guideline of the DGGG, OEGGG and SGGG (S3-Level, AWMF Registry No. 015/083, December 2020) - Abou-Dakn, Michael; Schäfers, Rainhild; Peterwerth, Nina; Asmushen, Kirsten; Bässler-Weber, Susanne; Boes, Ulrike; Bosch, Andrea; Ehm, David; Fischer, Thorsten; Greening, Monika; Hartmann, Katharina; Heller, Günther; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Purpose This guideline aims to summarize the current state of knowledge about vaginal birth at term. The guideline focuses on definitions of the physiological stages of labor as well as differentiating between various pathological developments and conditions. It also assesses the need for intervention and the options to avoid interventions. The second part of this guideline presents recommendations and statements on care during the dilation and expulsion stages as well as during the placental/postnatal stage. Methods The German recommendations largely reproduce the recommendations of the National Institute for Health and Care Excellence (NICE) CG190 guideline Intrapartum care for healthy women and babies. Other international guidelines were also consulted in individual cases when compiling this guideline. In addition, a systematic search and analysis of the literature was carried out using PICO questions where necessary, and other systematic reviews and individual studies were taken into account. For easier comprehension, the assessment tools of the Scottish Intercollegiate Guidelines Network (SIGN) were used to evaluate the quality of additionally consulted studies. Otherwise, the GRADE system was used for the NICE guideline, and the evidence reports of the IQWiG were used to evaluate the quality of the evidence. Recommendations Recommendations and statements were formulated based on identified evidence and/or a structured consensus.
CRIS-Team Scopus Importer:2022-11-25
Keywords: delivery; guideline; term; vaginal birth